Web-SCADA for Monitoring and Controlling Hybrid Wind-PV Power System - Aryuanto Soetedjo; Yusuf Ismail Nakhoda; Abraham Lomi; Farhan Farhan (Universitas Ahmad Dahlan, 2014)
This paper presents the implementation of Web-SCADA on the hybrid wind-PV power system. Both the electrical paramaters such as current, voltage, power and the environment parameters such as wind speed, solar irradiation, and PV temperature are monitored remotely via Internet using a web browser. The SCADA system allows the user to control the hybrid power system remotely. The low cost sensor systems, RTUs and PLC are developed for implementing the SCADA system. The IntegraXor SCADA is employed as the Web-SCADA software. It provides the easy way for developing the Web-based SCADA application. The experimental results show that the Web-SCADA works properly in the monitoring and controlling the hybrid power system. The developed sensor systems provides the average error of 2.87%. The developed RTUs are able to acquire the sensor data and communicate with the SCADA server in real-time.